The Effect of Learning Style, Emotional Intelligence, and Adversity Quotient on the Second-grade Students’ Mathematics Learning Achievement of Islamic Senior High School - Ainun, Rezki Awalia; Rosidah; Hamda (EduLine: Journal of Education and Learning Innovation, 2022)
This research aims to determine the effect of learning style, emotional intelligence, and adversity quotient on the second-grade students’ mathematics learning achievement of Islamic Senior High School. The type of this research is ex post facto, where the total sample used is 100 students selected using random sampling technique. The data was obtained through a learning style questionnaire, emotional intelligence, adversity quotient, and mathematics learning achievement tests. The data were analyzed using descriptive statistics and inferential statistics using multiple linear regression analysis. The result showed that: (1) There is no difference in the type of learning style in affecting students’ mathematics learning achievement. (2) Students’ emotional intelligence has a positive but not significant effect on their mathematics learning achievement. (3) Students’ Adversity quotient has a positive but not significant effect on their mathematics learning achievement. (4) Learning style, emotional intelligence, and adversity quotient have no significant effect on students’ mathematics learning achievement.